OPTIMALISASI APLIKASI SEHAT INDONESIAKU PTM MELALUI PENGUMPULAN DATA CERDIK PADA MASYARAKAT DI KELURAHAN DESA POPODU KECAMATAN BULANGO TIMUR PROVINSI GORONTALO - HANDAYANI, LILIS; Daud, Ayudhita Cahyani; Bilondatu, Maimun (Indonesian Journal of Health Information Management Services, 2024)
Non-communicable diseases are a major health problem in Indonesia. So that the management of the implementation of the Integrated Non-Communicable Disease Coaching post-activity is a very important part of the early detection of each NCD. The Indonesian Ministry of Health has launched the ASIK application as a strategy for early detection of NCD cases. CERDIK behavior is also effective in improving non-communicable disease prevention and control behavior in terms of cognition, attitudes, and skills. Based on interviews with the head of the health center in Bulango Timur sub-district, it is known that data collection on non-communicable diseases has not been carried out. And the use of the ASIK application has not been fully utilized. The methods used are community education through the CERDIK instrument and the substitution of science and technology with the ASIK Application. Based on data entry in the ASIK application, it is known that lack of physical activity is 16 people, lack of consumption of vegetables and fruit is 32 people, excessive oil and fat consumption is 103 people, excessive salt consumption is 90 people, consuming alcohol is 13 people, exposed to cigarette smoke is 50 people, smoking is 39 people, hyperglycemic is 2 people, pre-diabetes is 13 people, and hypercholesterol is 7 people. The results of this data are easier to use for early detection of NCD cases, even though the examination can be done through self-assessment. And also, the ASIK application can be used for reporting from community health centers and monitoring by the Health Office.